Developing donors of ultra-early maturity in barley - I. A. Zveinek; O. N. Kovaleva (Труды по прикладной ботанике, генетике и селекции)
Background. The length of the growing season is a limiting factor in many regions with unstable climatic conditions. The development of ultra-early barley donors makes it possible to accelerate the breeding process aimed at producing commercial cultivars adapted to cultivation area requirements.Materials and methods. The donors Kibel, Kibel uluchshenny, Kibtsel and Kibkor were obtained through individual selection of barley forms combining earliness and productivity from the hybrid combination Belogorsky × k-15881. The experiments were carried out according to the approved guidelines. Yield components were used to calculate the index of productivity for the donors versus the reference cv. ‘Belogorsky’.Results and conclusions. Earliness is controlled in the donors by three recessive genes. The donors’ period from emergence to heading was 7–9 days shorter than that of the reference cv. ‘Belogorsky’, with a low norm of reaction, which attested to their high adaptability. The resulting barley forms were highly resistant to lodging. The donor Kibel uluchshenny in all spike yield components did not differ from the reference. The other donors were close to the reference in spike length and 1000 seed weight. The example of Kibel uluchshenny was used to demonstrate the possibility of producing barley forms combining high earliness and good productivity. The developed donors may prove useful in the breeding for earliness in the areas where the length of the growing season is a limiting factor.